Students’ Teaching Competency Preparedness in Attending Field Experience Practice - Purwasih, Joan Hesti Gita; Sholichah, Anif Fatimatus; Pratiwi, Seli Septiana (International Journal of Research in STEM Education, 2021)
This research focuses on the readiness and the lack of students’ competence as pre-service teacher in dealing with field experience practice (PPL). The research was carried out using a mix method. Researchers develop research designs using qualitative method first, and then explain the findings obtained more comprehensively using qualitative method. The results of quantitative research were obtained through questionnaires, while qualitative data were obtained through interviews and literature studies. The results of the study show that the low competence of students is in three domains, that are 1) mastery of making learning tools, 2) determining learning strategies and models, and 3)mastering materials.